Loganin Exerts Sedative and Hypnotic Effects via Modulation of the Serotonergic System and GABAergic Neurons - Shi, Rui; Han, Yan; Yan, Yu; Qiao, Hao-Yi; He, Jun; Lian, Wen-Wen; Xia, Cong-Yuan; Li, Ting-Li; Zhang, Wei-Ku; Xu, Jie-Kun (Frontiers in Pharmacology, 2019)
Corni fructus, the fruit of Cornus officinalis Sieb. et Zucc., has been used as a tonic for the kidney in China for thousands of years. Loganin is one of the major constituents derived from Corni fructus. In this study, we revealed the sedative and hypnotic activity of loganin and investigated its mechanisms for the first time. Pentobarbital-induced sleep test and insomnia mice models (induced by caffeine and p-chlorophenylalanine (PCPA)) were used for the assessment of sedative and hypnotic effects of loganin. It was found that loganin (20-50 mg/kg) exerted sedative effect in normal mice. Loganin exhibited hypnotic effect by increasing sleep onset and sleep duration in pentobarbital-treated mice, recovering PCPA-induced insomnia and exerting synergistic hypnosis effect with 5-HTP. In addition, electroencephalograph (EEG) and electromyography (EMG) recordings of rats showed that loganin (35 mg/kg) prolonged the ratio of non-rapid eye movement (NREM) sleep and shortened wakefulness significantly, further immunohistochemistry showed that loganin (35 mg/kg) increased c-Fos expression in GABAergic neurons of rats in the ventrolateral preoptic nucleus (VLPO). The levels of norepinephrine (NE), dopamine (DA), serotonin (5-HT) and its metabolite were measured in the hippocampus, prefrontal cortex and striatum of mice, 1 h after loganin (35 mg/kg) treatment. 5-HT, 5-HIAA/5-HT, DA and DOPAC were decreased significantly in the prefrontal cortex. In conclusion, these results indicated that loganin produced beneficial sedative and hypnotic activity, which might be mainly mediated by modification of the serotonergic system and GABAergic neurons.